Oral Candidiasis in Immunosuppressed Wistar Rats (Rattus norvegicus) Post Dexamethasone Injection at 7.2 mg/kg and 16 mg/kg Doses - Al Abrori, Ucy Nur Hamida; Ayuningtyas, Nurina Febriyanti; Ernawati, Diah Savitri; Hendarti, Hening Tuti; Surboyo, Meircurius Dwi Condro; Radithia, Desiana (Brazilian Dental Science, 2020)
Objective: Oral candidiasis is an infection that occurs in the oral cavity and is caused by candida species, often Candida albicans. This infection commonly occurs in a condition of immunosuppression caused by dexamethasone. Due to the side effects of antifungal therapy, developing a standardized immunosuppressed animal model to induce oral candidiasis for new therapies is required. The aim of this study is to observe oral candidiasis in immunosuppressed Wistar rats post dexamethasone injection at 7.2 mg/kg and 16 mg/kg doses. Material and Methods: Twenty-one Wistar rats were divided into three groups: control group, treatment group 1 (injected with dexamethasone at a concentration of 7.2 mg/kg), and treatment group 2 (at a concentration of 16 mg/kg) for five days. Immunosuppression status was observed by leukocyte count and all the subjects’ palates were inoculated with C.albicans 0.1 ml of 15x108 UFC/ml 24 hours later. The subjects’ tongues were observed and confirmed by laboratory examination on day 10. A statistical analysis was performed using one way ANOVA, Kruskal–Wallis, Tukey HSD, and Mann-Whitney U tests. Results: A significant clinical appearance of the subjects’ tongues was observed only between C and T1 (p=0.023;p